2013
DOI: 10.1186/1471-2164-14-262
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants in locally raised Chinese chicken genomes determined using array comparative genomic hybridization

Abstract: BackgroundCopy number variants contribute to genetic variation in birds. Analyses of copy number variants in chicken breeds had focused primarily on those from commercial varieties with nothing known about the occurrence and diversity of copy number variants in locally raised Chinese chicken breeds. To address this deficiency, we characterized copy number variants in 11 chicken breeds and compared the variation among these breeds.ResultsWe presented a detailed analysis of the copy number variants in locally ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 48 publications
6
27
2
Order By: Relevance
“…Moreover, these enriched GO terms were mainly involved in cellular regulation and structure, various binding functions as well as stress and immune responses, which are consistent with several previous studies [9,[32][33][34], suggesting that the copy number variable genes may influence the responses to external stimuli and provide the mutational flexibility to adapt rapidly to changing selective pressures due to evolutionary adaption [59]. Most CNVRs also spanned some QTL regions, which indicated that these CNVRs may exert significant effects on traits of economic interest in chickens.…”
Section: Promising Candidate Genes Covered By Cnvrssupporting
confidence: 79%
See 3 more Smart Citations
“…Moreover, these enriched GO terms were mainly involved in cellular regulation and structure, various binding functions as well as stress and immune responses, which are consistent with several previous studies [9,[32][33][34], suggesting that the copy number variable genes may influence the responses to external stimuli and provide the mutational flexibility to adapt rapidly to changing selective pressures due to evolutionary adaption [59]. Most CNVRs also spanned some QTL regions, which indicated that these CNVRs may exert significant effects on traits of economic interest in chickens.…”
Section: Promising Candidate Genes Covered By Cnvrssupporting
confidence: 79%
“…The NGS technology and RD method employed in our work has advantages in both technology platform and genetic diversity compared with the eight previous reports [9,[32][33][34]36,[39][40][41]. Because a significant fraction of CNVs falls into genomic regions not well-covered by microarrays, especially for SD regions lacking sufficient probes [16,23], CNV as a major source of genetic variation is complementary to SNP and could account for a substantial part of missing heritability [14].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The causative mutation should be located in this 18.9 kb region, and no structural change in this region was identified in the present study via Sanger sequencing or in our previous study using array CGH [25]. The sequence of the assembly gap in this region (GenBank KC166241) contained 83.5% G and C with numerous poly G, poly C and CpG sites.…”
Section: Resultsmentioning
confidence: 67%